Generative adversarial networks synthetic optical coherence tomography images as an education tool for image diagnosis of macular diseases: a randomized trial - Peng, Jie; Xie, Xiaoling; Lu, Zupeng; Xu, Yu; Xie, Meng; Luo, Li; Xiao, Haodong; Ye, Hongfei; Chen, Li; Yang, Jianlong; Zhang, Mingzhi; Zhao, Peiquan; et al. (Frontiers in Medicine, 2024)
Purpose: To evaluate the assessment of generative adversarial networks (GANs) synthetic OCT images as an education tool for image diagnosis of macular diseases in medical students and ophthalmic residents training.In this randomized trial, twenty fifth-year medical students and 20 ophthalmic residents were enrolled and randomly assigned (1:1 allocation) into Group real OCT and Group GANs OCT.All participants had a pre-test to show their educational background, followed by a 30-minutesmartphone-based GANs/real OCT images-based education program for macular diseases recognition training. Another two tests were scheduled five minutes and one week after the training to test their short-term and long-term performances. Scores and time consumptions were recorded and compared. After all tests, an anonymous subjective questionnaire was acquired.In Group GANs OCT, scores improved from 80.0 (46.0 to 85.5) to 92.0 (81.0 to 95.5) five minutes after training (p<0.001) and 92.30± 5.36 one-week after training (p<0.001). Similarly, in Group real OCT, scores improved from 66.00 ± 19.52 to 92.90 ± 5.71 (p <0.001), respectively. No significant difference was found for scores of tests, score improvements and time consumptions between Group GANs OCT and Group real OCT. Medical students had significantly higher score improvement after training than residents(p<0.001) did.The education tool using synthetic OCT images had a similar educational ability compared to that using real OCT images, which improved the interpretation ability of ophthalmic residents and medical students in both short-term and long-term performances. The smartphonebased educational tool could be widely promoted for educational applications.